Impact of Nutrition on Non-Coding RNA Epigenetics in Breast and Gynecological Cancer - Krakowsky, Rosanna H. E.; Tollefsbol, Trygve O. (Frontiers in Nutrition, 2015)
Cancer is the second leading cause of death in females. According to the American Cancer Society, there are 327,660 new cases in breast and gynecological cancers estimated in 2014, placing emphasis on the need for cancer prevention and new cancer treatment strategies. One important approach to cancer prevention involves phytochemicals, biologically active compounds derived from plants. A variety of studies on the impact of dietary compounds found in cruciferous vegetables, green tea and spices like curry and black pepper have revealed epigenetic changes in female cancers. Thus, an important emerging topic comprises epigenetic changes due to the modulation of noncoding RNA levels. Since it has been shown that noncoding RNAs such as microRNAs and long noncoding RNAs are aberrantly expressed in cancer and furthermore are linked to distinct cancer phenotypes, understanding the effects of dietary compounds and supplements on the epigenetic modulator noncoding RNA is of great interest. This article reviews the current findings on nutrition-induced changes in breast and gynecological cancers at the noncoding RNA level.